Volume 3B: Heat Transfer 2013
DOI: 10.1115/gt2013-95639
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and CFD Studies of NGV Endwall Cooling

Abstract: For engines operating at high turbine entry temperatures it is increasingly important to cool the high pressure nozzle guide vane (HP NGV) endwalls. This is particularly so for low NOx combustors operating with flatter outlet temperature distributions. Double-row arrangements of film/ballistic cooling holes upstream of the NGV passage have been employed in production engines. Optimisation of such systems is non-trivial, however, due to the complex nature of the flow in the endwall region. Previo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…Thomas et al, 1 describe experimental validation of the CFD methods presented in this study: experimental maps of endwall eff obtained at a number of coolant to mainstream mass flux ratios, showing good agreement with CFD predictions. Implementation in FLUENT and validation.…”
Section: Implementation Of Scalar Tracking Methods In Cfdmentioning
confidence: 64%
See 3 more Smart Citations
“…Thomas et al, 1 describe experimental validation of the CFD methods presented in this study: experimental maps of endwall eff obtained at a number of coolant to mainstream mass flux ratios, showing good agreement with CFD predictions. Implementation in FLUENT and validation.…”
Section: Implementation Of Scalar Tracking Methods In Cfdmentioning
confidence: 64%
“…A two-passage CFD domain was used to simulate flow through a test cascade. The geometry of the cascade is that used in a large-scale platform cooling test facility in Oxford University, 1 which includes a linearised NGV geometry from a recent commercial engine. Geometric details of the cascade are provided in Table 1.…”
Section: Implementation Of Scalar Tracking Methods In Cfdmentioning
confidence: 99%
See 2 more Smart Citations
“…Takeishi et al [8] studied the influence of secondary flows in the passage on endwall film cooling and found that the endwall film cooling jets were deflected from the pressure side to the suction side. Thomas et al [9] conducted experimental and numerical investigation of 1st stage vane endwall film cooling and found that due to the complex vortex and effect of pressure gradient, the areas close to leading edge and pressure side as well as the region around trailing edge were difficult to be cooled. Wright et al [10] showed that the vortices formed upstream of the blade cascade would greatly reduce the endwall film cooling effectiveness.…”
Section: Introductionmentioning
confidence: 98%